CBCT Analysis of Mandibular Ramus as a Donor Site for Cortical Bone Graft: A Retrospective Analytical Study - Pallabi Das; Samiran Ghosh; Kaushik Dutta; Richi Burman; Amit Ray; Debolina Pramanick; Siddhartha Chatterjee; Somak Saha (Journal of Clinical and Diagnostic Research)
Introduction: Sufficient volume of bone is of prime importance for successful osseointegration of dental implants. The mandibular ramus acts as a good source of cortical bone graft with fewer complications compared to harvesting from the mandibular symphysis or body. Aim: To evaluate the maximum extent and different dimensions of cortical bone graft that can be harvested from the ascending ramus of the mandible while maintaining a safe zone from anatomical vital structures by using Cone Beam Computed Tomography (CBCT). Materials and Methods: A retrospective analytical study was carried out in the Department of Oral and Maxillofacial Surgery, Guru Nanak Institute of Dental Sciences and Research, Kolkata, West Bengal, India from February 2021 to September 2022. CBCTs of 30 patients were used to study 55 sites of the ascending ramus of the mandible. The CBCTs were collected from the institutional archive. The studies were done using NewTom Viewer (NNT) viewer software. The dimensions measured in the present study included length, height, thickness, surface area and volume of the bone graft. Each dimension was compared among genders, sides and different age groups (18-29 years, 30-45 years and >45 years). Statistical Package for Social Sciences (SPSS) version 22.0 was used for statistical analysis. Continuous variables (Mean, Median and Standard Deviation) were compared using Mann-Whitney U test or Kruskal Wallis Test as appropriate. Results: Among 55 sites, 25 (45.5%) were from female candidates and 30 (54.5%) were from males. A total of 56.4% (n=31) of the sites were from the right side and 24 (43.6%) were from the left side. The sites were divided into three age groups: 18-29 years 18 (32.7%), 30-44 years 24 (43.6%) and ≥45 years 13 (23.6%). The mean length of cortical bone graft that can be harvested from the mandibular ramus was found to be 14.49±2.66 mm, whereas the mean height and thickness were 6.40±2.07 mm and 3.04±0.61 mm, respectively. The mean surface area was found to be 308.88±75.37 sq mm, whereas the volume was 272.15±92.02 cu mm. Statistically significant differences were found for surface area and volume between genders, with males having greater dimensions than females. Conclusion: The mandibular ramus can be an excellent option for harvesting cortical bone grafts for alveolar ridge augmentation procedures. The maximum dimensions of the ramus bone graft observed in the present study will help surgeons decide whether to harvest the ramus graft according to the size of the defect present.